(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article discusses the creation of a new simulation model of cyclones that clean machines from dust during primary cotton processing. The results of theoretical and practical studies of ways to increase the efficiency of cyclones using the latest computer technologies and software are presented. The ratio of centrifugal force and gravity, which strikes the internal surfaces of the cyclone at an average speed and moves dusty air particles of different sizes, is compared. Theoretical studies carried out to study the composition of dusty air, which represents fibrous waste, are presented.